y=(mx-4/3)(x-3)
A[4/(3m),0),B(3,0)
x=0,y=4,C(0,4)
若AC=BC
因为CO垂直BC,所以他也是底边中线
所以 AO=BO=3
A(-3,0)
4/(3m)=-3
m=-4/9
若BC=AB
由勾股定理
BC=√(BO^2+CO^2)=5
所以AB=|3-4/(3m)|=5
3-4/(3m)=5,3-4/(3m)=-5
4/(3m)=-2,4/(3m)=8
所以m=-2/3,m=1/12
若AC=AB
则AC=√(AO^2+CO^2)=√(16/9m^2+16)
AB=|3-4/(3m)|
√(16/9m^2+16)=|3-4/(3m)|
平方
16/9m^2+16=9-8/m+16/9m^2
16=9-8/m
m=-7/8
所以m=-4/9,-2/3,1/2,-7/8
所以
y=-4x^2/9+4
y=-2x^2/3+2x/3+4
y=x^2/2-6x/17+4
y=-7x^2/8-31x/24+4
a在x的正半轴上,b在负半轴上
所以x1*x2=-(m+1)-1
|a|=3|b|
设y=0的两个根是x1,x2
x1+x2=3a-a=2a=2(m-1)
a=m-1
x1*x2=3a*(-a)=-3a^2=-(m+1)
-3(m-1)^2=-(m+1)
3m^2-7m+2=0
m=2,m=1/3
m=1/3,y=-x^2-4x/3+4/3,但此时y=0时x分别=-2和2/3,不合题意,舍去.
所以m=2,y=-x^2+2x+3